What Has Been Seen Cannot Be Unseen-Detecting Auxin In Vivo - Pařízková, Barbora; Pernisová, Markéta; Novák, Ondřej (International journal of molecular sciences, 2017)
Auxins mediate various processes that are involved in plant growth and development in response to specific environmental conditions. Its proper spatio-temporal distribution that is driven by polar auxin transport machinery plays a crucial role in the wide range of auxins physiological effects. Numbers of approaches have been developed to either directly or indirectly monitor auxin distribution in vivo in order to elucidate the basis of its precise regulation. Herein, we provide an updated list of valuable techniques used for monitoring auxins in plants, with their utilities and limitations. Because the spatial and temporal resolutions of the presented approaches are different, their combination may provide a comprehensive outcome of auxin distribution in diverse developmental processes.
Keywords: auxin; auxin distribution; direct visualization; auxin signalling; Indoleacetic Acids; indirect visualization; vývoj rostlin; Gene Expression Regulation, Plant; Plant Development; receptor; kyseliny indoloctové; regulace genové exprese u rostlin; Arabidopsis; auxin transport; sensor